People with Autism and The Propensity for Law-Breaking: A Special Education Teachers’ Perspective - Mohd Kusrin, Zuliza; Rosliza-Murni, Abrahman; Yusof, Wafaa; Nasohah, Zaini; Samuri, Mohd Al Adib; Muhd Adnan, Nurul Ilyana; Dahalan, Zahidah (UUM Press, 2023)
Autism is a subtype of neuro-developmental disorders, that causes the afflicted person to have social skills deficit, which then manifests into their behaviours. Behaviours that are typical among persons with autism, such as obsessions with daily routine, difficulties in understanding abstract matters and codes of conduct may expose them to engage in indecent acts in public or exhibit other forms of risky behaviours that violate social norms and break the law. The objective of this research is to study the behaviour of persons with autism who tend to break the law based on the perspective of teachers at autism centres in Malaysia. Data were collected through focus group discussion (FGD) with 25 special education teachers who were directly involved in the process of early intervention and education of children with autism. Data obtained were then analyzed descriptively and thematic analysis was conducted to obtain the recurring themes. Results of FGD demonstrated that the frequently emerging themes of rule-breaking behaviors committed by persons with autism are physically hurting others, setting buildings on fire (arson), vandalism of public property, theft, sexual and cyber offences which are considered criminal acts under the Penal Code and the Shariah Criminal Offences State Enactment/Act. Most research participants, however, considered these behaviors to be part of the individual with autism behavior and thus do not consider them serious enough to report to law enforcement for investigation and prosecution. Thus, it is recommended that teachers, parents, and caretakers be more attentive to preventing high-risk behavior of persons with autism through ongoing early intervention programs tailored to meet the needs of persons with autism. Research findings can help society to better understand autistic behavior that needs timely intervention, so it will not lead to an investigation by the police or criminal prosecution.